The association between negative affect and physical activity among adults in a behavioral weight loss treatment. (March 2020) - Kerrigan, Stephanie G.; Schumacher, Leah; Manasse, Stephanie M.; Loyka, Caitlin; Butryn, Meghan L.; Forman, Evan M.
Abstract: Introduction: Many individuals engaged in behavioral weight loss make suboptimal increases in moderate-to-vigorous physical activity (MVPA). Theoretically, reductions in negative affect could reinforce MVPA. However, little work has been done investigating the association between facets of negative affect (e.g., average levels of negative affect, variability in negative affect) and MVPA among individuals attempting to increase MVPA as part of a behavioral weight loss attempt. Methods: Participants ( n = 139) provided data at month 6 of a year-long behavioral weight loss program (at which point the prescription for MVPA had reached the highest level). Participants wore an accelerometer and provided EMA ratings of affect over the same week. Results: Individuals engaged in more frequent and longer periods of MVPA had lower average negative affect and variability in negative affect across the assessment period. Lower negative affect one day predicted greater time spent in MVPA on the next day; lower variability in negative affect than one's average level also predicted greater time spent in MVPA on the next day. Greater engagement in MVPA than one's own mean on one day did not predict mean or variability in affect. Discussion: Engaging in MVPA over time may reduce negative affect, while lower negative affect may increase motivation to engage in MVPA. Importantly, day-to-day effects indicated that affect is an important acute predictor of MVPA behavior. It is possible that individuals, particularly those with higher negative affect or variability in negative affect, may benefit from the inclusion of skills to manage negative affect in programs prescribing physical activity. Highlights: Average levels physical activity are negative associated with negative affect. Physical activity is negative associated with variability in negative affect. Lower variability in affect is associated with greater physical activity the next day. Negative affect may be important to address among those adopting physical activity.